A study on adsorption of gases in the thin film nanocomposites. (2019) - Niranjana, K.; Jerald Maria Antony, G; Raja, S.
Abstract: Separation of greenhouse gases through polymeric thin film by the selective transport of gas are immense advantages such as light weight, economical, high process flexibility and less space requirement. The thin film technology is used in post combustion process as well as pre combustion processes. This thin film mixed matrix composites (MMC) is prepared using inorganic nanofiller and polymer matrix. In this study, the effect of Lanthanum Oxide (La2 O3 ) nanofiller on the N2 gas adsorption properties of polysulfone (PSf) composite is reported. The solvent evaporation technique is used for synthesizing the film composite. To complete the polymerization of the thin film, the film kept in oven at 90°C for 210 minutes. The morphology of the thin film composite is investigated by Field Emission Scanning Electron Microscope (FESEM) and the chemical structure of the composite is also confirmed through Fourier transform infrared spectroscopy (FT-IR). The performances of the thin film on adsorption are characterized by gas adsorption techniques in measurement of N2 gas. The La2 O3 thin film composite significantly improved (31%) N2 gas adsorption when compared to the neat thin film